(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Friction stir welding (FSW) is proved as a promising welding technology for joining dissimilar aluminium alloys. Aluminium alloys are used extensively within the aerospace industry for applications such as fuselage and wing skin panels due to their high strength to weight ratio. Therefore, an effort is made to optimize the process parameters of FSW using Al 6061 and Al 7075 alloys by the Minitab 16 program in order to enhance tensile properties such as elongation (E), yield stress (YS), and ultimate tensile strength (UTS). Grey relational analysis (GRA) based on the Taguchi method is applied using two factors tool rotational speeds (TRS) and welding speed (WS) with four levels. Results show that the variables, namely the tool rotation speed and welding speed have a significant effect on yield stress, ultimate tensile strength and elongation. Results also show that the Taguchi based grey relational approach improved properties of output response of welded Al 6061 and Al 7075 aluminum alloys.